2013
DOI: 10.1002/jbm.b.33050
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo evaluation of tissue‐based biomaterials in a rat full‐thickness abdominal wall defect model

Abstract: Hernias are defects in which an anatomical fascia is breached resulting in ectopic positioning of an organ into an orifice which routinely does not contain it. Intervention often involves repositioning translocated organs and repair of damaged fascia using exogenous grafts. Despite hernia prevalence, repairs can still fail due to postoperative complications, such as chronic pain and decreased mobility. This study compared repair capacities and characterized the foreign body response elicited by a number of her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 34 publications
0
36
0
2
Order By: Relevance
“…Parietene™ showed the least shrinkage at 30 days after implantation (8(1‐25) per cent). Strattice™ and Omyra ® Mesh showed the least shrinkage 90 days after implantation (15 (13–20) and 15 () per cent respectively). Strattice™ showed the least shrinkage 180 days after implantation (13 (5–17) per cent).…”
Section: Resultsmentioning
confidence: 96%
“…Parietene™ showed the least shrinkage at 30 days after implantation (8(1‐25) per cent). Strattice™ and Omyra ® Mesh showed the least shrinkage 90 days after implantation (15 (13–20) and 15 () per cent respectively). Strattice™ showed the least shrinkage 180 days after implantation (13 (5–17) per cent).…”
Section: Resultsmentioning
confidence: 96%
“…Once grafted in vivo, our results showed that SCTLAS were properly integrated in the host abdominal wall tissues with no signs of rejection, infection or other complications, thus suggesting that the bioengineered tissues were highly biocompatible, whereas control SM displayed some signs of inflammatory reaction mainly consisting of macrophage cells. Previous works demonstrated that synthetic SM may exert immediate and chronic inflammatory responses after in vivo implantation, although these responses depend on the properties of each individual mesh . In fact, a recent report suggests that the in vivo use of biomaterials could be associated to a foreign body reaction with several phases and stages that may include a chronic inflammation phase with the presence of abundant macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…However, dermis grafts showed lower cell infiltration, degradation and new tissue formation than those of SIS and bladder 20,151-153 , prolonging graft remodelling over 12 months 152,153 . This longer degradation may be due to the higher organisation and density of dermis compared to SIS or bladder.…”
Section: In Vivo Assessment Of Host Response To Collagen-based Devicesmentioning
confidence: 92%
“…However, this response was normalised between all grafts over extended periods 153,165 . Regarding cell infiltration, mononuclear cells were detected around Permacol™ and only infiltrated through material pores; only 20% of implants were colonised at day 14 and the totality of graft was colonised after 1 month 152,165,166 . At 90 days, Permacol™ showed a higher amount of macrophages (RAM-11 positive, specific antibody for rabbit macrophages) and FBGCs than non-cross-linked SIS graft (Surgisis™), but slightly lower macrophage recruitment than other cross-linked porcine dermis graft (CollaMend™) 166 .…”
Section: In Vivo Assessment Of Host Response To Collagen-based Devicesmentioning
confidence: 98%